Bridging the Digital Divide: Community-Based Digital Innovation for Inclusive Socioeconomic Development - Napat Chai; Aom Thai; Pong Krit; Ma’rifani Fitri (Yayasan Adra Karima Hubbi, 2026)
Digital transformation has accelerated economic growth and social connectivity, yet persistent digital inequalities continue to marginalize vulnerable communities from meaningful participation in the digital economy. Access to infrastructure alone has proven insufficient to ensure inclusive socioeconomic development, as disparities in digital literacy, institutional support, and local innovation capacity remain significant barriers. This study aims to examine how community-based digital innovation initiatives contribute to bridging the digital divide and promoting inclusive socioeconomic outcomes. A mixed-methods, multi-site comparative design was employed involving 180 participants across three underserved regions. Quantitative data were collected through digital literacy assessments and socioeconomic surveys, while qualitative insights were obtained through interviews, focus groups, and field observations. Inferential statistical analyses revealed significant improvements in digital literacy, income levels, employment stability, and entrepreneurial engagement (p < 0.001). Regression results indicated that digital literacy gains significantly predicted income growth, while qualitative findings highlighted the mediating role of participatory governance and social capital. The study concludes that community-based digital innovation serves as an effective structural mechanism for translating digital access into sustainable economic empowerment. Integrating grassroots capacity-building with digital infrastructure investment is essential for achieving equitable and resilient socioeconomic development in digitally evolving societies.